2013
DOI: 10.1007/s00439-013-1364-6
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a reference group for distal 18q-: clinical description and molecular basis

Abstract: Although constitutional chromosome abnormalities have been recognized since the 1960s, clinical characterization and development of treatment options have been hampered by their obvious genetic complexity and relative rarity. Additionally, deletions of 18q are particularly heterogeneous, with no two people having the same breakpoints. We identified sixteen individuals with deletions that, despite unique breakpoints, encompass the same set of genes within a 17.6 Mb region. This group represents the most genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 23 publications
4
27
0
4
Order By: Relevance
“…For example, with del(15)(q11.2), although the breakpoints are clustered, the phenotypic presentation ranges from apparently normal to moderate intellectual disability with a constellation of associated malformations (Vanlerberghe et al, ). More similar to the current study are the heterogeneous distal deletions of the long arm of chromosome 18q (18q‐ syndrome), some phenotypic features are nearly 100% penetrant, while others are observed in only a minor fraction of the patients (Cody et al, ). One possibility is that the variability in the presentation of patients with this deletion may be due to the presence of a modifier gene(s) either within or outside of the 10q26.3 region that affects the expressivity of specific features.…”
Section: Discussionsupporting
confidence: 84%
“…For example, with del(15)(q11.2), although the breakpoints are clustered, the phenotypic presentation ranges from apparently normal to moderate intellectual disability with a constellation of associated malformations (Vanlerberghe et al, ). More similar to the current study are the heterogeneous distal deletions of the long arm of chromosome 18q (18q‐ syndrome), some phenotypic features are nearly 100% penetrant, while others are observed in only a minor fraction of the patients (Cody et al, ). One possibility is that the variability in the presentation of patients with this deletion may be due to the presence of a modifier gene(s) either within or outside of the 10q26.3 region that affects the expressivity of specific features.…”
Section: Discussionsupporting
confidence: 84%
“…Although each individual has a unique region of hemizygosity, there is a group of individuals whose breakpoints are between two genes that are 1.76 Mb apart. Because this is as as close to a recurrent genotype as we have detected and because these individual's deletions are about average in size compared to our entire cohort with terminal deletions we have referred to this as the Distal 18q‐ Reference Group [Cody et al, ]. Their region of hemizygosity is shown in Figure .…”
Section: Molecular Characterizationmentioning
confidence: 78%
“…The individuals with interstitial hemizygosity have FISH confirmed interstitial deletions. The position of the TCF4 gene; which has a significant phenotypic, effect is indicated as is the hemizygous region for the18q‐ Reference Group described previously [Cody et al, ].…”
Section: Molecular Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A group of over 290 individuals with a terminal or interstitial deletion of 18q was analyzed using aCGH, and no overlaps of the deleted regions were found [Heard et al, 2009]. More than half of 16 individuals of the previous group with terminal deletion of 18q, with a breakpoint upstream CDH7 , have delayed myelination of the brain, foot anomalies, atretic and stenotic ear canals, hypospadias in males, tapered fingers, flat midface, proximally placed thumbs, and congenital heart anomalies [Cody et al, 2014]. Using the UCSC genome browser (http://genome.ucsc.edu) and the OMIM database (http://www.omim.org/), we observed that the deleted region of 18q22.1 between 65,612,478 and 68,326,910, as in our patient, includes the CDH7 , CDH19 , DSEL protein-coding genes.…”
Section: Discussionmentioning
confidence: 99%